Criminal Law Reform in Indonesia: An Analysis of Supervisory Sentences and the Principle of Balance: Pembaharuan Hukum Pidana di Indonesia: Analisis Tentang Pidana Pengawasan dan Asas Keseimbangan - Afifah Firdaus; Indra Yugha Koswara (Lex Renaissance, 2024)
The criminal law reform agenda in Indonesia requires a comprehensive analysis to develop criminal supervision policies. In Law Number 1 of 2023 concerning the Criminal Code, supervision crime is considered a basic type of crime. To ensure fairness in sentencing, various points of view need to be considered, including procedures for implementing supervision over criminal supervision. The aim of this research is to analyze changes in criminal law policy in Indonesia. The method used is normative legal research with a statutory approach. The research results in this study state that the paradigm change in the criminal system from retributive, which is repressive, to restorative, based on justice. This is reflected in the national Criminal Code which includes the crime of supervision as a new type of crime that is an alternative to the crime of conditional deprivation of liberty. Judicial integration is very important to ensure that the implementation of criminal supervision in the future runs effectively and does not become a new burden in criminal law enforcement in Indonesia.Keywords: Criminal Law Reform, Criminal Supervision, Policy. AbstrakAgenda pembaharuan hukum pidana di Indonesia diperlukan analisis yang komprehensif untuk mengembangkan kebijakan pidana pengawasan. Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana mengkategori pidana pengawasan sebagai jenis pidana pokok. Untuk memastikan keadilan dalam pemidanaan perlu dipertimbangkan berbagai sudut pandang, termasuk prosedur pelaksanaan pengawasan terhadap pidana pengawasan. Tujuan penelitian ini adalah menganalisis terhadap perubahan kebijakan hukum pidana di Indonesia. Jenis penelitian ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan. Hasil penelitian menunjukkan bahwa perubahan paradigma dalam sistem pemidanaan dari retributif yang bersifat represif menjadi restoratif yang berbasis keadilan. Hal ini tercermin dalam KUHP nasional yang mencakup pidana pengawasan sebagai jenis pidana baru yang bersifat alternatif terhadap pidana perampasan kemerdekaan bersyarat. Integrasi peradilan sangat penting untuk memastikan bahwa pelaksanaan pidana pengawasan di masa mendatang berjalan dengan efektif dan tidak menjadi beban baru dalam penegakan hukum pidana di Indonesia.Kata kunci: Kebijakan, Pembaharuan Hukum Pidana, Pidana Pengawasan.